University Students' Tendency to Use Educational Videos for English Learning - Miftahul Candrika Kumara Muslimah; Zulfah Fakhruddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The rapid development of digital technology has transformed English as a Foreign Language (EFL) learning through the integration of educational videos as flexible learning resources. While previous studies have mainly examined the effectiveness of educational videos and students’ perceptions of technology integration, limited attention has been given to students’ tendency to use educational videos and its relationship with learning engagement. Therefore, this study aimed to investigate university students’ tendency to use educational videos for English learning and examine its relationship with learning engagement. A quantitative correlational design was employed involving 100 students of the English Education Study Program at IAIN Parepare. Data were collected through a structured questionnaire and analyzed using descriptive statistics and Pearson Product-Moment Correlation. The findings showed that students demonstrated a high tendency to use educational videos (M = 3.84) and a high level of learning engagement (M = 3.58). Furthermore, a strong positive relationship was found between students’ tendency and learning engagement (r = .766, p < .001). These findings suggest that educational videos are closely associated with students’ engagement in English learning and provide insights into digital learning behavior within Technology-Enhanced Language Learning (TELL) environments.